1984
DOI: 10.1051/jphys:0198400450110176500
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic viscosity of flexible macromolecules : transition from theta to collapsed state

Abstract: 2014 Des mesures de viscosité intrinsèque [~] sont effectuées sur des solutions diluées de polystyrène dans le cyclohexane en fonction de la température (T ~ 0) et de la masse moléculaire (8,2 x 104 ~ Mw ~ 2,06 x 107). Le facteur d'expansion (03B13~ = [~]/[ ~03B8]) de la viscosité intrinsèque obéit à une loi d'échelle dont la variable réduite est (T 2 0 1 4 0 3 B 8 / T) • Mw Lorsque (T 2 0 1 4 0 3 B 8 / T) • M w ~ 2 0 1 4 4 0 , la viscosité intrinsèque d'une chaîne effondrée est indépendante de la masse molécu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1985
1985
1997
1997

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 25 publications
(50 reference statements)
1
15
0
Order By: Relevance
“…We must have AT > 8/N 1 ~~ to reach a significant collapse [3]. The final state has been widely studied experimentally [4][5][6][7][8] and theoreticallystarting from an idea of Stockmayer [9]. Here we shall use the simplest (mean field) theoretical description [10,11] to describe the collapse.…”
Section: Aims and Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…We must have AT > 8/N 1 ~~ to reach a significant collapse [3]. The final state has been widely studied experimentally [4][5][6][7][8] and theoreticallystarting from an idea of Stockmayer [9]. Here we shall use the simplest (mean field) theoretical description [10,11] to describe the collapse.…”
Section: Aims and Toolsmentioning
confidence: 99%
“…For a very long polystyrene chain (M = 107), taking AT/0 = 10-1 we arrive at time r~ ~ 1 millisecond. In practice, one would probably prefer pressure jumps to temperature jumps, especially for lower molecular weights M. Experimentally, in the PS/cyclohexane system (7,8), for AT/AT* > 40 and a molecular weight of 10', precipitation occurs at concentrations 5 10-5 g/cm3.…”
Section: Practical Aspectsmentioning
confidence: 99%
“…Relaxation of the solvent was achieved by random displacement Monte Carlo moves. Statistics for conformational properties, i.e., mean square end-to-end distance, ͗R 2 ͘, and mean square gyration radius, ͗R g 2 ͘, were collected for O(10 7 ) steps after an equilibration period of at least 5ϫ10 6 steps. This recipe gives O(10 6 ) successful chain moves.…”
Section: A Canonical Ensemble Simulationsmentioning
confidence: 99%
“…On the experimental side, there has been a great deal of work on the dynamic and static properties of dilute polymer solutions in good, theta, and poor solvents near the UCST. 1,6 As is well-known, polymer solutions also exhibit lower critical solution temperature ͑LCST͒, or thermally induced, phase separation where phase splitting is induced by raising temperature. LCSTs have been observed in strongly interacting polar mixtures, for example aqueous solutions, as well as in weakly interacting nonpolar polymer solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments on the transition from a single polymer coil behavior in the O state to a globule in the collapsed state did not agree with one another (Slagowski, Tsai & Mclntyre, 1976;Nierlich, Cotton & Farnoux, 1978;Bauer & UUman, 1980;Pritchard & Caroline, 1980;Miyaki & Fujita, 1981;Oyama, Shiokawa & Baba, 1982;Post & Zimm, 1982;Stepanek, Konak & Sedlacek, 1982;Perzynski, Adam & Delsanti, 1982;Perzynski, Delsanti & Adam, 1984;Vidakovic & Rondelez, 1984;Selser, 1985;Chu, Park, Wang & Wu, 1987). If we consider the collapsed state based on the radius of gyration Rg from static lightscattering measurements, recent experiments on the PS/CY system below the Ou temperature and the PS/methyl acetate (MA) system both below the Ov temperature and above the lower theta temperature (OD showed that a plateau 3 1/2 region [with constant (es IzlMw )3 could be reached in a plot of scaled expansion factor 3 1/2 o~ IzlMw versus scaled reduced temperature I'rlM 1/2 where ~= Rg(T)/Rg(O) and z = IT-O[/O.…”
Section: Coil-to-globule Transitionmentioning
confidence: 99%